Computational intelligence-based time series forecasting - Du, Liang (Nanyang Technological University, 2023)
Time series forecasting is a crucial area of data science that is essential for decision-making across multiple domains such as transportation, finance, meteorology, and energy management. Computational Intelligence (CI) provides a flexible approach to solve forecasting tasks that is not limited to traditional statistical, machine learning, or deep learning-based methods. This thesis proposes three novel CI-based forecasting paradigms to deal with various forecasting scenarios.